Choice and perceptions of exercise: A test of three moderating variables. (September 2018) - Caplandies, Fawn C.; Brown, Jill A.; Murray, Ashley B.; Rose, Jason P.; Geers, Andrew L.
Abstract: Objectives: This study tested whether choice over ostensibly different exercise bike programs alters the positivity of an exercise experience, attitudes towards exercising, post-exercise mood, intentions to engage in exercise in the future, and desire to receive more information about exercise. Further we assessed whether the influence of choice-making on these dependent measures was moderated by the number of choice options, choice instrumentality, and domain familiarity. Design: One-hundred fifty participants that varied in their use of bikes for exercise were randomized into a 3 (choice options) x 2 (choice instrumentality) between-subjects design. Participants' prior experience exercising on a bike was recorded and used as an additional predictor variable. Methods: For the choice options manipulation, participants either made no choice or decided between 2 or 5 ostensibly different exercise bike programs. For the choice instrumentality manipulation, half of the participants were told that their program selection could improve their bike riding experience, whereas the other half were not given this information. All participants exercised on a stationary bike in the laboratory for a 10-min period using the same standardized program. Results: Choice options and exercise bike familiarity interacted to determine outcomes. Specifically, opportunity for choice increased positive exercise experience, attitudes towards physical activity, exercise intentions, and the desire to receive more information—but only among those who had prior experience using a bike to exercise. Conclusions: Results provide support for the use of choice as a technique for increasing liking and intentions toward exercise for those with prior experience with the exercise activity. Highlights: Among bike users, choice improved exercise bike experience and intentions. Among bike users, intentions to exercise were increased with choice. Choice is moderated by familiarity, not number of choice options or instrumentality. Feelings of choice can be a viable strategy for changing exercise perceptions.